Pre-COVID-19 short sleep duration and eveningness chronotype are associated with incident suicidal ideation during COVID-19 pandemic in medical students: a retrospective cohort study - Dandan Zheng; Dandan Zheng; Dandan Zheng; Qingsong Qin; Yingyin Peng; Hao Zhong; Yerui Huang; Hongjie Wang; Qiqing Tan; Yun Li; Yun Li; Yun Li (Frontiers Media S.A., 2024)
IntroductionCross-sectional evidence suggests that sleep problems increased the risk of suicide during the 2019 coronavirus disease (COVID-19) pandemic. However, a lack of longitudinal studies examined the relationship between pre-COVID-19 sleep duration, chronotype and incident suicide during the COVID-19 pandemic. Thus, we examined these associations in a longitudinal study of medical students.MethodsFrom the Shantou College Student Sleep Cohort, a total of 333 first and second grade medical students (age 19.41 ± 0.82 years, female 61.26%), without suicidal ideation (SI) at pre-COVID-19 period, were followed up during the COVID-19 pandemic. Incident SI was defined by their response to the 9th question from the Beck Depression Inventory. Short sleep duration was defined as less than 7 h/night. The Morningness-Eveningness Questionnaire was used to evaluate the participants' chronotype. Logistic regression with adjusted odds ratios (AOR) and 95% confidence intervals (95% CI) was used to examine the association between sleep and SI.ResultsThe incidence of SI during the COVID-19 pandemic was 5.71%. Logistic regressions with confounding factors adjustment showed that both short sleep duration (AOR = 4.91, 95% CI = 1.16-20.74) and eveningness (AOR = 3.80, 95% CI = 1.08-13.30) in the pre-COVID-19 period were associated with increased risk of incident SI during the COVID-19 pandemic.ConclusionPre-COVID-19 short sleep duration and eveningness predict incident SI during the COVID-19 pandemic in medical students. Prolonging sleep duration may help to decrease SI during major public health crises.